The Performance of CSR Mutual Funds and Investment Decision-Making - Jen-Der Day; Thuy Mai Trinh Nguyen; Chia Nan Wang; George Yungchih Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Nowaday, Corporate Socially Responsible (CSR) mutual funds are becoming a popular investment option for investors. However, no any research confirms whether CSR Mutual fund activity is better than market index or not. Besides, we should have one method can help con sequently investors in making the decision to select appropriate investment funds. In this study, we measure the financial performance of a sample of 15 CSR mutual funds in the world, with the monthly return over the period 2008-2013, then we propose the dession table. We first use the measures to evaluate the performance of mutual funds such as Alpha (α), Sharpe Ratio (SR), and Information Ratio (IR). And then, we use the obtained decision table to evaluate the predictability by each measure. The results indicate that only 3 of the 15 CSR mutual funds achieve good performance results based on the statistical significance of the two measures Sharpe Ratio and Information Ratio. In addition, the IR is suggested to evaluate and make investment decisions in the future and it also is the best one among the three measures. The decision table suggest investors a measure forecast accuracy way.